Exploring the adoption of modern hives among stingless beekeeping in Sabah, Malaysia: The approach of diffusion of innovation theory - V. S., Sumin; F. J., Langkan; H. A., Damit; Mohd Effendi, Wasli; N. A., Besar (IOP Publishing, 2024)
Stingless beekeeping is crucial for Malaysia's socio-economic development and environmental conservation, providing sustenance, materials, and income. Despite its potential, conventional practices such as obtaining stingless bee colonies through tree logging will disrupt ecosystems and threaten native pollinators. This study focuses on Sabah's stingless beekeepers, examining factors influencing the adoption of sustainable modern hives essential for boosting honey production and additional colony sales. However, current use of modern hives remains limited due to beekeepers' lack of interest. The Diffusion of Innovation Theory suggests the need for a sustainable approach. The results of this study show that most beekeepers use conventional hives such as log and honey box hives (87.7%), bamboo hives (59.6%), and single box hives (55.3%), while sustainable options like MARDI hives (55.3%), Mustafa hives (33.3%), and SIRIM ceramic hives (3.5%) are less common but align with guidelines for sustainable stingless beekeeping. The results discovered five latent factors that influence the respondents’ to adopt modern hives which are Compatibility, Trialability, Observability, Relative Advantage and Complexity or Simplicity with 85.31% total cumulative variance explained. These findings highlight the importance of promoting sustainable hive adoption to bolster the industry's growth and environmental sustainability. By enhancing modern hive adoption, the stingless beekeeping industry can achieve ecological, economic, and social sustainability, contributing to Malaysia's conservation efforts and economic growth.